Analisis Ekonomi Alternatif Pengelolaan Ekosistem Mangrove di Kecamatan Bintan Timur Kabupaten Bintan - Tince Sofyani (Ilmu Perairan (Aquatic Science), 2009)
The aims of the research are : 1). to identify both the potential and the typesof utilizations of mangrove ecosystem carried out by the local society, 2). to analyzethe economic values of the mangrove ecosystem, and 3). to analyze the alternativesof the strategic utilization for mangrove ecosystem. The number of respondents is58 deriving from fishery household (RTP) and non RTP. The data were thenanalyzed by using consumer surplus, Total Economic Value (TEV) and MultiCriteria Analysis (MCA).The results show that biggest utility is the one of crabs that reaches Rp113,647,959 with the surplus consumer of Rp 27,780,612. The highest optimumprofit from arang bakau utilization amounts to Rp 360,732 for 11 (eleven)households, while the lowest profit is obtained from the utilization of prawn pondwith Rp 424,839. The biggest proportion is from the indirect utilization with apercentage of 85,58 % with a value of Rp 116,375,900,400 per year. Furthermore,the Total Economic Value of the mangrove forest ecosystem in East Bintan Districtcovering 2 ha for ponds, 1100 ha for HPHH licency and 3354,29 ha of mangroveforest amounts to Rp 135,977,965,849 per year. The utiliation alternatives put aspriorities, based on the balance between indicators for both efficiency criteria andecology criteria, between the efficience and equity criteria in the level oef interestrate 0f 10 % are as follows : firstly, utilization alternativ III (100 % mangroveforest), secondly, utilization alternative II (1100 ha mangrove forest by licencyHPHH and 33356,29 ha mangrove forest. Nevertheless, the utilization alternativ Ican not be given as choices in this management because utilization of prawn pondnot efficient.